The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1177/070674370605100309
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Psychological Problems in the Elderly

Abstract: Objective: To determine the prevalence of mood, anxiety, and other disorders in the population of Canadians aged 55 years and over. Method:We undertook an analysis of the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2).Results: There was a linear decrease for all disorders after age 55 years. This was true for men and women; for anglophones, francophones, and allophones; and for both people born in Canada and people who immigrated to Canada after age 18 years. Consistent with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
45
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 17 publications
11
45
1
Order By: Relevance
“…Finally, the negative effect of age on disorder, 31 the nonsignificance of sex differences, 12,13,32 and the lower prevalence of disorder observed in French-speaking Canadians 16 have been reported before in this population. Several explanations, including cohort effects, selective attrition, methodological problems, age-related hormonal changes, and other aging differences have been offered for declining prevalence of disorder with age and for the disappearance of the gender gap that is invariably found among younger adults.…”
Section: Discussionsupporting
confidence: 55%
“…Finally, the negative effect of age on disorder, 31 the nonsignificance of sex differences, 12,13,32 and the lower prevalence of disorder observed in French-speaking Canadians 16 have been reported before in this population. Several explanations, including cohort effects, selective attrition, methodological problems, age-related hormonal changes, and other aging differences have been offered for declining prevalence of disorder with age and for the disappearance of the gender gap that is invariably found among younger adults.…”
Section: Discussionsupporting
confidence: 55%
“…Nationally representative (US) [93] (NESARC) Cairney [22] (CCHS) Corna [33] (CCHS) Streiner [166] ( Schaub and Linden [6] 516 Representative community sample…”
Section: 205mentioning
confidence: 99%
“…This contrasts with previous work which has shown that individuals with poor language proficiency have higher rates of depression, anxiety, and substance abuse compared to those with good to excellent language proficiency. [2][3][4] However, in these studies participants had at least limited English skills and data collection took place in the United States where there is a pre-eminence of English as an "official language". In contrast, the current study was unable to assess English or French language proficiency and took place in Canada where two official languages exist.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some linguistic minority groups have been shown to have an increased risk for poor mental health. [2][3][4] However, it should be noted that the relationship between language and mental health outcomes has been inconsistent. [5][6][7][8] This may be attributed to the fact that research occurring in Canada and the United States has almost exclusively focused on visible minority groups or immigrants as a proxy for language use.…”
mentioning
confidence: 99%